Infrared organic light-emitting diodes with carbon nanotube emitters - Graf, Arko; Zakharko, Yuriy; Zaumseil, Jana (Advanced materials, 2018)
While organic light-emitting diodes (OLEDs) covering all colors of the visible spectrum are widespread, suitable organic emitter materials in the near-infrared (nIR) beyond 800 nm are still lacking. Here, the first OLED based on single-walled carbon nanotubes (SWCNTs) as the emitter is demonstrated. By using a multilayer stacked architecture with matching charge blocking and charge-transport layers, narrow-band electroluminescence at wavelengths between 1000 and 1200 nm is achieved, with spectral features characteristic of excitonic and trionic emission of the employed (6,5) SWCNTs. Here, the OLED performance is investigated in detail and it is found that local conduction hot-spots lead to pronounced trion emission. Analysis of the emissive dipole orientation shows a strong horizontal alignment of the SWCNTs with an average inclination angle of 12.9° with respect to the plane, leading to an exceptionally high outcoupling efficiency of 49%. The SWCNT-based OLEDs represent a highly attractive platform for emission across the entire nIR.
Gesehen am 14.05.2019